An honest lie - Fisher, Tarryn (Graydon House, 2022)
"When Rainy reluctantly agrees to a girls' weekend in Vegas, she's prepared for an exhausting parade of shots and slot machines. But after a wild night, her friend Braithe doesn't come back to the hotel room. And then Rainy gets the text message, sent from Braithe's phone: someone has her. But Rainy is who they really want, and Rainy knows why. What follows is a twisted, shocking journey on the knife-edge of life and death. If she wants to save Braithe--and herself--the only way is to step back into the past."--